Patterns of Students' Macroscopic, Submicroscopic, and Symbolic Representation Ability in Acid-Base Topic - Mujibaturrahmi Mujibaturrahmi; Sri Winarni; Latifah Hanum (EduChemia (Jurnal Kimia dan Pendidikan), 2022)
Abstract concepts of chemicals are generally presented in three chemical representation levels: macroscopic, submicroscopic, and symbolic. This study aims to; (1) evaluate each representation ability; (2) determine how to evaluate the pattern of representational abilities; and (3) evaluate the patterns of each student's macroscopic, submicroscopic, and symbolic representation abilities. Qualitative descriptive has been used as the design of this study. Twenty-one multiple-choice questions based on macroscopic, submicroscopic, and symbolic representations have been designed with validation results from two experts, which are 100% valid, and with the Kuder Richardson formula (K-R 20), the reliability value is 0.84. The subjects in this study were all students of class XI MIPA at SMA Negeri 8 Banda Aceh. The research was conducted online via a google form. The results showed that students with high categories of macroscopic, submicroscopic, and symbolic representation skills were 61, 18, and 51%, respectively. 9.8% of students can master the three levels of representation with high criteria. The pattern of representation ability is mainly owned by 24.4% with high macroscopic and symbolic representation abilities but low submicroscopic representation abilities. Because submicroscopic representation lags macroscopic and symbolic, explanation in chemistry should always involve submicroscopic representations other than macroscopic and symbolic.